Rationalization Rain Gauge Density using the Stepwise Method - Wahyuni, Sri; Sisinggih, Dian; Kriswardhana, Willy; Widyaningrum, Aprilia; Atika , Yumna (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
Establishing and maintaining hydrometeorological networks in sub-watersheds is challenging. An analysis of an established network of Rain Gauge Station (RGS) is provided in this study in the form of a comprehensive statistical framework. Hydrometeorological observations are monitored by this network, which aims to gather the most pertinent information while minimizing expenditures. The study location is at Ngasinan Hulu watershed (East Java, Indonesia), with ten rain gauge stations and one automatic water level recorder (AWLR). Errors in reviewing hydrological data in a watershed can cause the resulting data to be inaccurate. Therefore, to solve the problem of incorrect data, it is necessary to rationalize rain gauge stations. The rationalization for this study uses the Stepwise method. The results of the Stepwise-Enter method produce a combination of six rain gauge stations with measured rainfall data and a combination of four rain gauge stations with CHIRPS satellite rainfall data. Therefore, this combination of rain gauge stations is rational because it meets the classical assumption test, and the area is evenly distributed according to WMO standards.